Antibiotic Stewardship and Urinary Tract Infections in U.S. Nursing Homes Reporting to the National Healthcare Safety Network 2015–2016. (4th October 2017) - Kabbani, Sarah; Palms, Danielle; Bell, Jeneita; Hicks, Lauri; Stone, Nimalie
Abstract: Background: Urinary tract infections (UTIs), the most common infections reported in nursing homes (NHs), are often over diagnosed leading to inappropriate antibiotic prescribing. NHs enrolled in the National Healthcare Safety Network (NHSN) report UTIs meeting surveillance definitions and antibiotic starts (AS) for clinically treated UTI events. We describe the gap between NH reporting of NHSN-defined UTI events and clinically treated UTI. Methods: We performed a descriptive analysis of UTI events, AS, facility characteristics and antibiotic stewardship core elements reported by NHs submitting >1 month of UTI data into NHSN from January 2015 to December 2016. The facility UTI treatment ratio was calculated as total AS over total symptomatic catheter and non-catheter UTI events. We performed a bivariate analysis using Wilcoxon rank sum and chi-square tests to assess the relationship between reported NH characteristics, including implementation of antibiotic stewardship practices, and the facility UTI treatment ratio. For comparisons between groups, the outcome, UTI treatment ratio, was dichotomized as either <2 or >2. Results: During the reporting period, 158 unique NHs reported monthly UTI events into NHSN, median 9 months (IQR 4-18). Of 2, 221 UTI events reported, 22.3% were catheter-associated. The median UTI treatment ratio was 2.7 (IQR 1.2-8.0); 39.2% of all facilities reported implementing five antibiotic stewardship core elements (accountability, action, tracking, reporting and education). Comparing NHs that implemented all five core elements vs. <5, there was no association between core element implementation and the UTI treatment ratio ( P = 0.97). The following NH characteristics were significantly associated with a UTI treatment ratio >2 on bivariate analysis: for-profit ownership (OR 3.00, 95% CI 1.43-6.29), affiliation with a multi-facility organization (chain) (OR 6.38, 95% CI 2.48-16.44), and bed size ≥100 (OR 3.82, 95% CI 1.68-8.68). Conclusion: Large, for-profit, chain-affiliated NHs may be more likely to have a difference between clinically treated and NHSN-reported UTIs. Further evaluation of these findings with multivariate modeling is needed to assess how these specific factors may be associated with a UTI treatment ratio >2. Disclosures: All authors: No reported disclosures.